Artificial Intelligence in Product Design Education: Status, Benefits, and Challenges in the Tunisian Context - Fatnassi, Moâtaz (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2026)
This study examines the gradual integration of artificial intelligence (AI) into product design workshops at the École supérieure des sciences et technologies du design (ESSTED) [Higher School of Design Sciences and Technologies] in Tunisia. Using a mixed-method approach combining questionnaires and non-participant observations of project presentations, the study analyzes how AI is used across the different phases of the design process. The results indicate the use of AI predominantly in project research, analysis, and structuring phases, accompanied by a more limited and often implicit use during the ideation and prototyping phases. This trend is accompanied by a decline in traditional manual practices, particularly sketching. While AI is perceived as a means of improving project efficiency and consistency, significant cognitive, ethical, and pedagogical concerns have nevertheless been reported by both students and teachers. The study’s findings highlight the need for a structured pedagogical framework to facilitate the responsible and contextualized integration of AI, to strike a balance between technological innovation and the preservation of fundamental design skills.